An algebra problem by Carlos VP

Algebra Level pending

Find f ( x + 3 ) f ( x 1 ) f(x+3) - f(x-1) if f ( x ) = 2 x + 1 f(x)={ 2 }^{ x+1 }

2 x + 1 ( 9 ) { 2 }^{ x+1 }(9) 2 x ( 15 ) { 2 }^{ x }(15) 4 x ( 3 ) { 4 }^{ x }(3) 2 2 ( 1 ) { 2 }^{ 2 }(1)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Caleb Townsend
Mar 16, 2015

f ( x + 3 ) f ( x 1 ) = 2 x + 4 2 x = ( 2 x ) ( 2 4 ) 2 x = 2 x ( 2 4 1 ) = 2 x ( 15 ) f(x+3) - f(x - 1) = 2^{x + 4} - 2^x \\ = (2^x)(2^4) - 2^x \\ = 2^x (2^4 - 1) \\ = \boxed{2^x (15)}

Yeah , I guess so too but since this is a question based on Functional Equation , I think Calc suits it much better .

A Former Brilliant Member - 6 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...